Methods of Overcoming Professional Deformations Arising in the Activity of a Teacher - Ziyodullayev Daler Zahidjon ugli (Scientific Trends, 2024)
This article presents the causes of the professional deformation of pedagogues and various psychological disturbances in this process, and the factors for its elimination.
Keywords: Pedagogue, professional deformity, psychological health, burnout syndrome, emotional factors, psychoprophylactic measures.